Matrix metalloproteinase (MMP)-9: A realiable marker for inflammation in early human trichinellosis - Bruschi, F.; D’Amato, C.; Piaggi, S.; Bianchi, C.; Castagna, B.; Paolicchi, A.; Pinto, B. (Veterinary parasitology, 2016)
•Matrix metalloproteinase-9 (gelatinase B) increases in the sera of trichinellosis patients.•This gelatinase is a marker of inflammation in this parasitic disease, contrary to MMP-2 (gelatinase A).•The increase of gelatinase B has a clinical relevance in human trichinellosis. Matrix Metalloproteinases (MMPs) are involved in many physiological and pathological processes. As regards parasitic infections, the role of these proteins has been particularly studied in malaria, neurocysticercosis and angiostrongyloidosis. Recently, we evaluated serum levels of MMP-9 and -2 (gelatinases) in mice experimentally infected with Trichinella spiralis or Trichinella pseudospiralis, which cause different degrees of myositis and we found their significant increase in the former and, at a lesser extent, in the latter, thus suggesting the possibility that these gelatinases, particularly MMP-9, represent a marker of inflammation. Our aim was to evaluate the levels of MMP-9 and 2 in trichinellosis patients, to assess their possible clinical significance. Serum samples from 31 Trichinella britovi-infected individuals (20 males and 11 females), living in Tuscany, Central Italy, were analysed for MMP-9 and MMP-2 serum levels. Patients acquired infection with Trichinella after consuming raw or undercooked meat of wild boar. Their median age was 49±0.33years (range from 7 to 91). Sera was collected before starting anti-inflammatory treatment, aliquoted and stored at −20°C until use. Sera from healthy subjects was considered as controls. The gelatinolytic activity of MMPs was analysed by gelatin zymography on 8% polyacrylamide-SDS gels containing 0.1% porcine gelatin, under non-reducing conditions. Clear bands corresponding to the digested areas were evaluated with an appropriate software. MMP-9 levels were additionally determined in 15 patients using a commercial ELISA kit for human MMP-9. The zymographic analysis of the gels showed the presence in serum samples of gelatinase bands at approximately 125-kDa, 92-kDa and 72-kDa, corresponding to the MMP-9/Neutrophil gelatinase-associated lipocalin (NGAL) complex and proenzyme forms of MMP-9 and MMP-2, respectively. A significant (p<0.01) increase in gelatinolytic activity in patients compared to the control group was observed for pro-MMP-9 in 25 out of 31. The mean increase in activity was 39.25%±16.67%. No significant differences were observed for pro-MMP-2 activity. The MMP-9 levels detected by ELISA showed significant correlation with zymographic data (r2=0.62, p<0.003) and were higher in more affected patients (suffering diarrhea, facial edemas and myalgia). In conclusion, MMP-9 might be considered as a marker of inflammation in T. britovi patients. On the contrary, MMP-2 did not result significantly different in patients, compared to controls.